Effects of a Coordinative Ability Training Program on Adolescents’ Cognitive Functioning - Latino, Francesca; Cataldi, Stefania; Fischetti, Francesco (Frontiers in Psychology, 2021)
The purpose of this randomized controlled study was to investigate the effects of a 12-week coordinative ability training program on adolescents’ cognitive functioning, using evaluation tests of visuospatial perception, attention, and working memory. We randomly assigned 60 public school students (14–15 years) to either an experimental coordinative abilities training (∼40 min twice/week) group (n = 30) or a control group (n = 30) who received general psycho-physical wellness training (∼40 min., twice a week). At baseline and after training we used two standardized motor tests and a single cognitive measure (Corsi’s Block-tapping test) to assess students’ visuospatial perception, attention, and working memory. We found a significant Time x Group interaction for the Throwing and Catching Test and Corsi’s Block-Tapping test, reflecting a meaningful experimental group improvement (p < 0.001), and there were no significant pre-post changes found in the control group. Thus, a 12-week program of coordinative abilities was able to improve not only coordination skills but aspects of cognitive functioning relevant to academic achievement.